Diazoxide promotes oligodendrocyte precursor cell proliferation and myelination. - Birgit Fogal; Carolyn McClaskey; Sha Yan; Henglin Yan; Scott A Rivkees (PLoS ONE, 2010)
Several clinical conditions are associated with white matter injury, including periventricular white matter injury (PWMI), which is a form of brain injury sustained by preterm infants. It has been suggested that white matter injury in this condition is due to altered oligodendrocyte (OL) development or death, resulting in OL loss and hypomyelination. At present drugs are not available that stimulate OL proliferation and promote myelination. Evidence suggests that depolarizing stimuli reduces OL proliferation and differentiation, whereas agents that hyperpolarize OLs stimulate OL proliferation and differentiation. Considering that the drug diazoxide activates K(ATP) channels to hyperpolarize cells, we tested if this compound could influence OL proliferation and myelination.Studies were performed using rat oligodendrocyte precursor cell (OPC) cultures, cerebellar slice cultures, and an in vivo model of PWMI in which newborn mice were exposed to chronic sublethal hypoxia (10% O(2)). We found that K(ATP) channel components Kir 6.1 and 6.2 and SUR2 were expressed in oligodendrocytes. Additionally, diazoxide potently stimulated OPC proliferation, as did other K(ATP) activators. Diazoxide also stimulated myelination in cerebellar slice cultures. We also found that diazoxide prevented hypomyelination and ventriculomegaly following chronic sublethal hypoxia.These results identify KATP channel components in OLs and show that diazoxide can stimulate OL proliferation in vitro. Importantly we find that diazoxide can promote myelination in vivo and prevent hypoxia-induced PWMI.